Somalia : First Review Under the Staff-Monitored Program-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2019)
This paper discusses Somalia's First Review Under the Staff-Monitored Program (SMP). The report focuses on further efforts to mobilize revenues, including across the Federal Member States, strengthen public financial management, enhance financial sector stability, and strengthen compliance with the framework for anti-money laundering/ combatting the financing of terrorism. The authorities' strong commitment and program implementation has strengthened capacity despite a challenging environment. Underlying economic growth remains stable, supported by donor support and the ambitious and broad reform agenda. However, insecurity and recurring drought represent key risks to the outlook, and, despite progress, growth is insufficient to substantially reduce poverty. Financial stability reforms are deepening. New mobile money regulations are welcome, and implementation will be key for supporting financial stability. Continued efforts to expand the operational and organizational capacity of the Central Bank of Somalia will underpin further development of the financial sector more broadly. Reducing Somalia's debt to sustainable levels under the Heavily Indebted Poor Countries Initiative and normalizing relations with international financial institutions will unlock access to additional financial resources to address Somalia's development needs.